2011
DOI: 10.1111/j.1464-410x.2011.10632.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical outcome after high‐dose‐rate intensity modulated brachytherapy with external beam radiotherapy: 12 years of experience

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Biochemical control from series in which radical prostatectomy is performed for patients with unfavorable prostate cancer and/or low dose external beam radiation therapy are given remains suboptimal. The treatment regimen of HDR brachytherapy and external beam radiotherapy is a safe and very effective treatment for patients with high risk localized prostate cancer with excellent biochemical control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 40 publications
4
17
0
1
Order By: Relevance
“…Similar results were found in another study, reporting a bounce 15 months after treatment and biochemical failure, also defined using the Phoenix definition, after 28 months [18]. Another study reported a comparable mean time of 30 months for the occurrence of biochemical recurrence after HDR-BT + EBRT [23]. These findings indicate that increasing PSA levels within the first two years of follow-up are most probably benign PSA rises.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were found in another study, reporting a bounce 15 months after treatment and biochemical failure, also defined using the Phoenix definition, after 28 months [18]. Another study reported a comparable mean time of 30 months for the occurrence of biochemical recurrence after HDR-BT + EBRT [23]. These findings indicate that increasing PSA levels within the first two years of follow-up are most probably benign PSA rises.…”
Section: Discussionsupporting
confidence: 85%
“…This result differs from the latest publications in the literature which, though not supported by randomized prospective studies, indicated BRFS results in five, ten and fifteen years similar to surgery, external radiotherapy and brachytherapy in patients with low-risk prostate cancer. 15,24 It should be noted, however, that studies show that for implanted patients, BRFS rates are widely variable according to the selection criteria adopted, ranging from 63%, at 4 years, 29 to 93%, in five years. 30 With regard to operated patients, the BRFS also varies greatly due to the pathological findings, with global BRFS rates of 81% being reported in seven years.…”
Section: Resultsmentioning
confidence: 99%
“…15 In relation to operated patients, who had a less frequent follow-up, those with at least one annual dose of PSA in the follow-up period were assessed.…”
Section: Follow-upmentioning
confidence: 99%
“…Data with respect to predictors of distant metastasis outcomes following high-dose-rate brachytherapy are more limited [10]. Higher Gleason score has been a significant predictor of distant metastasis in most series, whereas total dose has not always been [1113]. Determining predictors of metastatic disease following combination therapy is important, because it identifies men who could benefit from additional treatment.…”
Section: Purposementioning
confidence: 99%